1985
DOI: 10.1002/jcp.1041230115
|View full text |Cite
|
Sign up to set email alerts
|

Clonal heterogeneity in colony stimulating factor production by murine T lymphocytes

Abstract: A panel of 55 alloreactive murine T-lymphocyte clones was screened for the production of granulocyte-macrophage colony stimulating factor (GM-CSF), multilineage CSF (multi-CSF), human-active eosinophil CSF (human-active EO-CSF), and interleukin 2 (IL-2) in response to stimulation with the lectin concanavalin A. Many clones were also characterized for cytolytic specificity and expression of the T-cell antigen receptor-associated surface markers Lyt-2 and L3T4, which reflect their specificity for Class I (H-2K, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 43 publications
2
31
1
Order By: Relevance
“…There is, however, some evidence for the coordinate induction of subsets of these genes. For example, GM-CSF, G-CSF, and IL-6 mRNAs are induced following TNF-ot treatment of fibroblasts and endothelial cells (40,53) and some mouse T-cell clones coordinately express GM-CSF and IL-3 (20). We have shown that the CK-1 sequence from the G-CSF gene is a TNF-a-responsive element in fibroblasts.…”
Section: Dnamentioning
confidence: 83%
“…There is, however, some evidence for the coordinate induction of subsets of these genes. For example, GM-CSF, G-CSF, and IL-6 mRNAs are induced following TNF-ot treatment of fibroblasts and endothelial cells (40,53) and some mouse T-cell clones coordinately express GM-CSF and IL-3 (20). We have shown that the CK-1 sequence from the G-CSF gene is a TNF-a-responsive element in fibroblasts.…”
Section: Dnamentioning
confidence: 83%
“…Under resting conditions, monocytic or T-cell production of CSFs is nonexistent or occurs at a low level (3). In response to activation, T cells produce granulocyte-macrophage CSF (GM-CSF) (23) and interleukin (IL)-3 (19), whereas monocytes produce granulocyte (G)-CSF, macrophage CSF (M-CSF; CSF-1), or GM-CSF (8, 14-16, 24, 28, 30). In parallel, IL-1 or tumor necrosis factor alpha treatment of primary cultures of fibroblasts (2,10,18,20,22,25), dermal fibroblasts, fibroblastic cell lines (29,34), and endothelial cells (30,35) results in de novo or increased CSF-1, G-CSF, and/or GM-CSF gene transcription.…”
mentioning
confidence: 99%
“…However, the extended conserved sequence of CK-1 and CK-2 noted above between GM-CSF and IL-3 genes may be involved in T-cell expression of these genes. It is noteworthy that IL-3 and GM-CSF are often coordinately expressed following Con A stimulation of murine T-cell clones (36).…”
Section: Specific Interaction Of Nuclear Proteins With the Promotermentioning
confidence: 99%